Pewarisan Nilai-Nilai Kearifan Lokal Untuk Memproteksi Masyarakat Bali Dari Dampak Kemajuan Teknologi - Ni Luh Ketut Sukarniti (Jurnal Ilmiah Cakrawarti, 2019)
The importance of maintaining local wisdom for Balinese people in order to face variousnegative impacts of social changes brought about by .Technology The symptom, which is basically feltby the Balinese today, is the fundamental socio-cultural change. The acceleration of the informationcoming along with the wave of technology has been significantly experienced by the Balinese, both atthe level of the “surface structure” (the attitudes and the pattern of behavior) and at the level of the“deep structure” (the value system, the life view, the philosophy, and the belief). The change is due tothe culture contacts between countries in which there are dialectic fight between the contemporaryvalues and those of the traditional where one tries to take the domination of another. Here, thehegemony and the neoliberal views are possibly coming and breaking all the aspects of life, includingthe values of the local culture ever obeyed firmly by the Balinese society. This condition leads to a spitand uncertain values situation because the people give more attention and respect to the modernvalues and marginalize the transcendental values. This is resulting in various violations of the moralvalues reflected by the feature, the style, and the life pattern of the society to occur. Therefore,reinforcement and inheritance of Balineselocal wisdom have to be conducted intensively to the Balineseyounger generation